Suprachiasmatic VIP neurons are required for normal circadian rhythmicity and comprised of molecularly distinct subpopulations - William D. Todd; Anne Venner; Christelle Anaclet; Rebecca Y. Broadhurst; Roberto De Luca; Sathyajit S. Bandaru; Lindsay Issokson; Lauren M. Hablitz; Olga Cravetchi; Elda Arrigoni; John N. Campbell; Charles N. Allen; et al. (Nature Communications, 2020)
Cell groups in the hypothalamic suprachiasmatic clock contribute to the genesis of circadian rhythms. The authors identified two populations of vasoactive intestinal polypeptide-expressing neurons in the suprachiasmatic nucleus which regulate locomotor circadian rhythm in mice.